2008
DOI: 10.1038/sj.bjc.6604307
|View full text |Cite
|
Sign up to set email alerts
|

CD133 expression is correlated with lymph node metastasis and vascular endothelial growth factor-C expression in pancreatic cancer

Abstract: Although CD133 has been shown to be a marker for cancer stem cells in various tumours, its expression in pancreatic cancer has not yet been clinically reported. In this study, we investigated the relationship between CD133 expression and clinicopathological factors in pancreatic cancer. Pancreatic head carcinoma specimens from 80 patients who underwent surgical resection were immunohistochemically assessed for CD133, vascular endothelial growth factor (VEGF)-C, CXCR4, CD34, Ki-67, and cytokeratin (CK) expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
140
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(164 citation statements)
references
References 54 publications
19
140
0
1
Order By: Relevance
“…Taken together, the specificity of our results is supported by previous studies in colorectal cancer. However, staining results, which differ from the positivity of the luminal surface in colorectal cancer, have recently been reported in pancreatic cancer, where a cytoplasmic expression of CD133 was shown (Hermann et al, 2007;Maeda et al, 2008). Such organspecific patterns of CD133 expression still have to be clarified in further studies.…”
Section: Discussionmentioning
confidence: 98%
“…Taken together, the specificity of our results is supported by previous studies in colorectal cancer. However, staining results, which differ from the positivity of the luminal surface in colorectal cancer, have recently been reported in pancreatic cancer, where a cytoplasmic expression of CD133 was shown (Hermann et al, 2007;Maeda et al, 2008). Such organspecific patterns of CD133 expression still have to be clarified in further studies.…”
Section: Discussionmentioning
confidence: 98%
“…Hermann et al reported that CD133+ cells were dramatically more resistant to gemcitabine and had highly tumorigenic and metastatic features [13]. In addition, it was shown that CD133 had significant role in prognosis of PDAC [46]. It was observed that the 5-year survival rate of patients with CD133-negative tumors was almost 5-fold higher than patients with less than 5% CD133-positive cells.…”
Section: Cd133mentioning
confidence: 76%
“…Pancreatic CSCs with CD133 expression demonstrated a higher metastatic potential compared with those without it (9). Stem cell-like glioma cells with CD133 expression promoted tumor angiogenesis has been reported to be associated with metastatic potential and poor survival in certain human malignancies (11,12). Vascular endothelial growth factor (VEGF) is intimately involved in the regulation of tumor-associated angiogenesis and has been reported to be associated with tumor aggressiveness, metastasis and poor prognosis (13).…”
Section: Introductionmentioning
confidence: 99%